Discovery and recovery of delta p-aminobenzoic acid. Issue 13 (5th February 2019) - Ward, Martin R.; Younis, Shatha; Cruz-Cabeza, Aurora J.; Bull, Craig L.; Funnell, Nicholas P.; Oswald, Iain D. H.
Abstract : A new high-pressure recoverable form has been observed in the model system, p -aminobenzoic acid. Abstract : We explore the polymorphism of p -aminobenzoic acid ( p ABA) under high-pressure conditions. We have been able to isolate a new high-pressure form (δ- p ABA) at pressures exceeding 0.3 GPa from three different pressure-transmitting media, water, water : ethanol and pure ethanol. We explore the compression behaviour of α- p ABA in each of these media using neutron powder diffraction and observe that the transition is kinetically hindered using the aqueous ethanol and ethanol solutions compared with the pure aqueous medium. δ- p ABA is sufficiently stable to be recovered to ambient pressure to enable its characterisation via X-ray powder diffraction and differential scanning calorimetry. At ambient pressure we have observed that δ- p ABA converts into α- p ABA on heating beyond 70 °C.